(untitled) (The South East European Journal of Economics and Business, 2019)
This paper deals with the influence of competition on soundness of Croatian insurers using the Boone indicator when measuring competition. The authors analyse Croatian insurers that operated over the pre-EU accession period 2008 – 2012 as well as in the period 2013 – 2017, i.e. after the accession to the EU. Several firm-level, industry-level and macroeconomic variables are used in the research. The findings of the analysis are twofold. Specifically, the Boone indicator reveals the impact of competition on the performance of efficient insurers in post-EU accession period only accounting for the reallocation effects proving that efficient insurers make higher profits. Regarding the determinants of the insurers’ soundness, premium to surplus ratio and inflation rate play significant role in pre - EU accession period whereas reinsurance and GDP growth rate are statistically significant after EU accession. Moreover, the competition increased in the years after the EU accession. Robustness check provides similar results.